RELIGIOUS AND MORAL VALUES IN MADURA FOLKTALES - Imron Wakhid Harits (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2014)
Madura has a lot of Folktales as the reflection of its values in its social life. As the cultural identity, most of Madura folktales are the mirror of social values and characteristics of Madura society. Thus, the Madura folktales contain the moral and religious values as the most important element for Madura society. The aim of this paper is to identify and to investigate five Madura folktales, these are: The Origin of Madura, Bangsadcara and Ragapadme, The Origin of Tajungan, Aer Mata Ebu, and Aryo Menak. These five folktales are chosen because they are the most popular Madura folktales among others. While, the aspects of moral and religious values are the most dominant elements that can be found in these five Madura folktales. Such two aspects are the local genious that can be bequeathed from one generation to the next generation. The aspect of moral will have the close relation with the appreciation and respecting to the parents and teacher on the other hand, the aspect of religious values are related with sufism and another Islamic values. Both of two aspects are used as the fundamental of social construction in Madura.